Evaluation of Sociopreneur-Based Curriculum Implementation in Santa Maria Vocational School with Iluminative Models - Margareta Dwi Wahyu Utari; Juwintar Febriani Arwan; Said Hamid Hasan (JPP (Jurnal Pendidikan dan Pembelajaran), 2022)
The purpose of this study is to analyze and evaluate the implementation of a social entrepreneur-based curriculum at Santa Maria vocational school. This study uses a qualitative method approach by applying an illuminative evaluative model using observations and interviews. Based on the results of the study, it was found that social entrepreneur-based curriculum planning in Santa Maria vocational school involves considerations and foundations that lead to the philosophical and social entrepreneurial goals. The implementation of the social entrepreneur curriculum runs with planning that is in line with the vision and objectives of the social entrepreneur curriculum in the education unit. The obstacles that occur indicate the internal motivation of students and they still need training related to social entrepreneur integration in subjects and their development in learning activities. Overall, this evaluation explains that the process of implementing a social entrepreneur-based curriculum can run well and receive positive responses from students and teachers.